Long noncoding RNA expression analysis in Crimean Congo hemorrhagic fever patients. Issue 7 (23rd March 2022) - Arslan, Serdal; Bakir, Mehmet; Bayyurt, Burcu; Aydemir, Eylem I.; Kinaci, Kenan; Engin, Aynur
Abstract: Crimean Congo hemorrhagic fever (CCHF) is an acute viral infection that can cause death. The detection of host transcriptome is important for understanding differences in the pathogenesis of the disease. Long noncoding RNAs (lncRNAs) regulate gene expression in different biological processes. They have also emerged as key molecules for therapeutic targets. We investigated the lncRNA gene expression profiles by utilizing the microarray for the first time in CCHF. LncRNAs were determined by the comparisons between case‐control, fatal case‐control, and fatal case‐nonfatal cases. Quantitative polymerase chain reaction was applied to validate the microarray results of some lncRNAs. In our study, 39 lncRNAs (5 downregulated and 34 upregulated) were found to be significantly regulated in the cases when compared to the controls ( p < 0.05; FC ≥ 2). One hundred ten lncRNAs exhibited a statistically significant difference between fatal cases and controls. FER1L4, ECRP, and LOC100133669 are important lncRNAs in both case and fatal case groups compared with controls. These lncRNAs may be considered important therapeutic targets for the CCHF in further studies.